Underlying Mechanisms of Chromatographic H/D, H/F, cis/trans and Isomerism Effects in GC-MS - Dimitrios Tsikas (Metabolites)
Charge-free gaseous molecules labeled with deuterium 2H (D) atoms elute earlier than their protium-analogs 1H (H) from most stationary GC phases. This effect is known as the chromatographic H/D isotope effect (hdIEC) and can be calculated by dividing the retention times (tR) of the protiated (tR(H) ) to those of the deuterated (tR(D)) analytes: hdIEC = tR(H)/tR(D). Analytes labeled with 13C, 15N or 18O have almost identical retention times and lack a chromatographic isotope effect. Derivatives of cis- and trans-analytes such as cis- and trans-fatty acids also differ in their retention times. Analytes that contain trans-C=C-double bonds elute earlier in gas chromatography-mass spectrometry (GC-MS) than their cis-C=C-double bonds containing congeners. The chromatographic cis/trans-effect (ctEC) can be calculated by dividing the retention times of the cis- by those of the trans-analytes: ctEC = tR(c)/tR(t). In the present work, the hdIEC and ctEC values of endogenous and exogenous substances were calculated from previously reported GC-MS analyses and found to range each between 1.0009 and 1.0400. The examination suggests that the H/D-isotope effects and the cis/trans-effects observed in GC-MS are based on differences in the inter-molecular interaction strengths of the analyte derivatives with the stationary phase of GC columns. The deuterium atoms, being larger than the H atoms of the analytes, attenuate the interaction of the skeleton of the molecules with the GC stationary phase. The angulation of trans-analytes decreases the interaction of the skeleton of the molecules with the GC stationary phase, as only parts of the molecules are close enough to the GC stationary phase to interact. Other chromatographic effects caused by hydrogen (H) and fluorine (F) atoms and by stereo-isomerism are considered to be based on a similar mechanism due to the different orientation of the side chains.